Noninvasive Evaluation of Clinically Significant Portal Hypertension in Patients with Liver Cirrhosis: The Role of Contrast-Enhanced Ultrasound Perfusion Imaging and Elastography - Zocco, Maria Assunta; Cintoni, Marco; Ainora, Maria Elena; Garcovich, Matteo; Lupascu, Andrea; Iezzi, Roberto; Annichiarico, Brigida Eleonora; Siciliano, Massimo; Riccardi, Laura; Rapaccini, Gian Ludovico; Grieco, Antonio; Pompili, Maurizio; Gasbarrini, Antonio (Ultraschall in der Medizin - European Journal of Ultrasound, 2022)
Background Hepatic venous pressure gradient (HVPG) is the gold standard for assessing the degree of portal hypertension (PH), but it is not suitable for routine clinical use. The recently developed ultrasonography techniques, dynamic contrast-enhanced ultrasound (D-CEUS) and liver stiffness (LS), have expanded the possibilities for noninvasive evaluation.Aims To investigate the usefulness of D-CEUS and elastographic parameters in assessing the presence and degree of PH.Methods This is a prospective monocentric study. Patients with liver cirrhosis referred for HVPG measurements underwent hepatic Doppler ultrasound, LS measurement, and D-CEUS with a second-generation contrast agent. Pearson’s correlation and a receiver operating characteristic (ROC) curve analysis were performed to assess the role of noninvasive findings in predicting clinically significant PH (CSPH) and severe PH (SPH).Results 46 consecutive patients (31 men; mean age±SD: 57±11 years) were enrolled. A significant positive correlation was noted between LS and HVPG (r = 0.809, p<0.0001) with an area under the ROC curve of 0.923. A cut-off value of 24.2 kPa best predicted CSPH with a positive predictive value of 85%. Among the D-CEUS features, the area under the ROC curves of liver parenchyma peak intensity (PI-LP) was greater than the other indices both for CSPH and SPH (1.000 and 0.981, respectively). A PI-LP under 23.3 arbitrary units indicated the presence of CSPH with a sensitivity and a specificity of 100%.Conclusion A multimodal ultrasound approach based on D-CEUS and LS might become a reliable predictor of CSPH and SPH and a useful alternative to HVPG.
Keywords: liver stiffness; clinically significant portal hypertension; liver cirrhosis; dynamic contrast-enhanced ultrasound